2010
DOI: 10.1111/j.1365-3083.2010.02460.x
|View full text |Cite
|
Sign up to set email alerts
|

Stimulatory Effect of LPS and Feedback Effect of PGE2 on IL-27 production

Abstract: Interleukin (IL)‐27 is a new member of the IL‐6/IL‐12 family, composed of two subunits, the Epstein–Barr virus–induced gene 3 (EBI3) and p28 chains (p28), and produced by activated monocytes and dendritic cells. IL‐27 plays an important role in the regulation of differentiation of naive T helper cells and has diverse effects on innate immune cells. However, the pro‐inflammatory mechanisms of IL‐27 are still not well known. In this study, we investigated the effect of lipopolysaccharide (LPS) on the production … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 47 publications
1
9
0
Order By: Relevance
“…Previously, we reported that PGE2 inhibited IL-27 expression in BMDCs (34), and Zhu et al (35) reported similar results in THP-1 cells. Here we report that PGE2 inhibition of IL-27 is similar in BMDCs, BMDMs, and splenic DCs, and that it occurs upon activation of various TLRs.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Previously, we reported that PGE2 inhibited IL-27 expression in BMDCs (34), and Zhu et al (35) reported similar results in THP-1 cells. Here we report that PGE2 inhibition of IL-27 is similar in BMDCs, BMDMs, and splenic DCs, and that it occurs upon activation of various TLRs.…”
Section: Discussionsupporting
confidence: 66%
“…Although the mechanisms involved in the induction of IL-27 in cDCs and macrophages have been studied extensively, little is known about factors and mechanisms that negatively impact IL-27 expression. We were the first to report that PGE2 inhibited IL-27 production by BMDCs (56), and a later publication reported on a similar finding in THP-1 cells (35). Here we report that PGE2 inhibits IL-27 production and p28 expression through a novel mechanism involving EP2/EP4-mediated cAMP increase, subsequent inhibition of irf1 expression and reduced IRF1 binding to the p28 promoter ISRE site.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Studies on knock-out mice deficient for individual EPs clearly revealed that PGE2 not only acts as a pro-inflammatory mediator, but also exerts anti-inflammatory responses (Sugimoto and Narumiya, 2007). In addition, recent investigations have demonstrated significant roles of PGE2 signaling, in particular EP2 and EP4 signaling, in innate and adaptive immune systems (Divangahi et al, 2010;Gagliardi et al, 2010;Mandapathil et al, 2010;Zhu et al, 2010). PGE2 is classically known as an immunosuppressant, because it inhibits helper T cell differentiation (Harris et al, 2002;Sugimoto and Narumiya, 2007).…”
Section: Possible Role Of Ep Signaling In the Cochlear Sensory Systemmentioning
confidence: 97%
“…However, the ginger extract may directly and/or indirectly influence the IL-27 production. For example, it has been reported that PGE2 (a production of COX-2) significantly inhibits LPS-induced IL-27 production by monocytic cell line (Zhu et al, 2010). On the other hand, the inhibitory effects of the ginger extract on the COX-2 have been demonstrated (Choi et al, 2013a).…”
Section: Pbs-treated Eaementioning
confidence: 98%